2012
DOI: 10.1007/bf03404072
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self-report and Health Care Provider Data to Assess Surveillance Definitions of Influenza-like Illness in Outpatients

Abstract: s part of most influenza surveillance systems, patients who meet specific symptom criteria will have culture samples taken for laboratory testing. 1,2 Several surveillance definitions of influenza-like illness (ILI) have been proposed. 2-6 The Centers for Disease Control and Prevention (CDC) in the United States defines ILI as the presence of fever (temperature of 38 degrees Celsius or greater) and one of either cough or sore throat or both, in the absence of a known cause other than influenza. 7 Health Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
3
0
3
Order By: Relevance
“…Nonetheless, to the best of our knowledge, no previous study has ever presented contact matrices according to gender. So far, gender differences in infectious diseases epidemiology have been attributed only to hormonal differences[ 28 ] or to differences in risk assessment[ 29 ] leading to incomplete reporting[ 30 ]. We suggest that the higher participation of women in infectious diseases such as influenza[ 31 ] or pertussis[ 32 ] could also be attributed to behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, to the best of our knowledge, no previous study has ever presented contact matrices according to gender. So far, gender differences in infectious diseases epidemiology have been attributed only to hormonal differences[ 28 ] or to differences in risk assessment[ 29 ] leading to incomplete reporting[ 30 ]. We suggest that the higher participation of women in infectious diseases such as influenza[ 31 ] or pertussis[ 32 ] could also be attributed to behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Schnepf's study of French ILI patients found that patients with no virus detected were less likely to have a cough (77.8%) than those with H1N1v (89.5%, p = 0.01) and more likely to have pharyngitis (21%) compared to those with H1N1v (10%, p = 0.003), but Schnepf was not able to predict PCR-positivity [19]. The Hutterite colony study found that combinations of fever, cough, sore throat and muscle aches predicted PCR influenza positivity, but the confidence intervals were wide [27]. The Indian Council of Medical Research influenza surveillance network study found that only three symptoms correlated with influenza PCR-positivity: cough (p < 0.0034), fatigue (p < 0.001) and chills/rigours (p < 0.001).…”
Section: Symptoms Assessed In Ili Surveys and Ability To Discriminatmentioning
confidence: 96%
“…The current study found that combining interviews and physical examination was important for predicting influenza test results [12]. While similar studies have been available to date, they have focused solely on symptoms, with only a few studies having analyzed a combination of interviews and physical examination [12,13].…”
Section: Discussionmentioning
confidence: 65%